# How do you find the derivative of #y=cos^-1(e^(2x))#?

Through implicit differentiation, you should have:

Hopefully this helps!

By signing up, you agree to our Terms of Service and Privacy Policy

To find the derivative of ( y = \cos^{-1}(e^{2x}) ), use the chain rule:

[ \frac{dy}{dx} = -\frac{1}{\sqrt{1 - (e^{2x})^2}} \cdot \frac{d}{dx}(e^{2x}) ]

[ \frac{dy}{dx} = -\frac{1}{\sqrt{1 - e^{4x}}} \cdot 2e^{2x} ]

[ \frac{dy}{dx} = -\frac{2e^{2x}}{\sqrt{1 - e^{4x}}} ]

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7